Rethinking the Notion of National Identity in the Novel The Redbreast by Jo Nesbo - Ivana Bančić ([sic])
This paper sets out to examine the extent to which the novel The Redbreast by Jo Nesbo confirms the hypothesis that in the 21st century the crime novel has become a platform suitable for the examination of national identity and the nature of violence in given social surroundings. The paper introduces the hypothesis that there is an undercurrent of unease perceivable in contemporary Norwegian society. The existence of the supporters of the Nazi regime in the history of the nation which after World War II has constituted itself as a modern, tolerant and multicultural society, causes a crisis of identity and evokes a new take-off of right-wing politics. Therefore, the policy of resistance to Nazism and the celebration of tolerance and multiculturalism are on slippery ground. But Nesbo's re-examination of national identity is not conducted solely for the purpose of questioning the absoluteness of ethical positions of good and evil; Nesbo transposes the contemporary Norwegian crime novel from the domain of subjective violence into the realm of objective violence. The paper argues that Nesbo explores the categories of the immoral and the righteous within Norwegian society, pinpointing thereby the dangers of a policy which uses the fear of immigrants as a means of mobilising the nation.